2014
DOI: 10.1371/journal.pone.0099157
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilization of Poly(Caprolactone) Copolymers through Introduction of Oligo(Ethylene Glycol) Moieties

Abstract: In this study, a new family of poly(ε-caprolactone) (PCL) copolymers that bear oligo(ethylene glycol) (OEG) moieties is described. The synthesis of three different oligo(ethylene glycol) functionalized epoxide monomers derived from 2-methyl-4-pentenoic acid, and their copolymerization with ε-caprolactone (CL) to poly(CL-co-OEG-MPO) copolymers is presented. The statistical copolymerization initiated with SnOct2/BnOH yielded the copolymers with varying OEG content and composition. The linear relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…42 Similarly, Wurth et al recently showed that the incorporation of oligo(ethylene glycol) side chains into PCL can reduce the water contact angle of films from ~90º to ~35º. 43,44 Dramatic increases in surface aqueous wettability have also been observed for electrospun amphiphilic scaffolds. Electrospun hydrophobic PLA and PLGA scaffolds have been characterized with water contact angles as high as 120º.…”
Section: Physical Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…42 Similarly, Wurth et al recently showed that the incorporation of oligo(ethylene glycol) side chains into PCL can reduce the water contact angle of films from ~90º to ~35º. 43,44 Dramatic increases in surface aqueous wettability have also been observed for electrospun amphiphilic scaffolds. Electrospun hydrophobic PLA and PLGA scaffolds have been characterized with water contact angles as high as 120º.…”
Section: Physical Propertiesmentioning
confidence: 96%
“…32 The tunable degradation rates, ease of processing and established medical uses of PLA and PLGA have made them attractive choices for integration with PEG to form amphiphilic di-block, 17,3337 tri-block, 3842 or multi-block copolymers. 4347 …”
Section: Typical Biodegradable Blocks Of Amphiphilic Block Copolymersmentioning
confidence: 99%
“…We have previously reported a simple and versatile approach to introduce functional elements along the aliphatic polyester backbone by copolymerizing lactones with α-ω-epoxy esters. 11 This copolymerization approach has been successfully exploited to introduce along PLA and poly(caprolactone) backbone many moieties such as hydrophilic polyethylene glycol (PEG) chains, 12 side groups with negative and positive charge, 13 and more recently chemical groups amenable to conjugation of biomolecules and dyes via click chemistry. 14 Building on these successes, in this study we synthesized epoxy esters of two of the most common lipid components of cells, namely octadecanol and cholesterol, with 2-methyl-4-pentenoic acid (MPA) (Figure S1 and Figure S2 in ESI), and copolymerized them with L-lactide using the tin-catalyzed ring opening copolymerization (ROP) to yield amorphous to semi-crystalline polymers with enhanced hydrophobicity (Figure 1).…”
mentioning
confidence: 99%
“…23 Adjusting the hydrophilic lipophilic balance (HLB) is one means to influence the material-cell interaction profile of polymers. 12 In this study we had theorized that the incorporation of cell lipid components into the PLA backbone would confer hydrophobic characteristics to the copolymers. The presence of a lipid rich surface was verified using attenuated total reflection-IR (ATR-IR) as discussed later (Figure 3B).…”
mentioning
confidence: 99%
“…Although PCL is a valuable biomaterial with important applications for drug‐delivery systems and bioresorbable scaffolds, several drawbacks such as low hydrophilicity, low melting point (≈60 °C), and relatively slow biodegradability impeded its extensive development . To overcome these drawbacks, basically two solutions are available: blending with other biomaterials, like hydrophilic polymers or synthesis of copolymers with improved properties . In the same time, melting point in the physiological range can be advantageous for specific biomedical applications, while slow degradation rate results in longer stability of the implants .…”
Section: Introductionmentioning
confidence: 99%